2006
DOI: 10.1016/s0022-5347(05)00048-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasonography for the Diagnosis of Testicular Injuries in Blunt Scrotal Trauma

Abstract: Scrotal ultrasonography, with the single radiographic finding of a heterogeneous echo pattern of the testicular parenchyma with loss of contour definition, is highly sensitive and specific in the diagnosis of testicular rupture in an otherwise equivocal scrotal examination. Accurate diagnosis and prompt repair led to a salvage rate for testicular rupture specifically of 83% and overall of 92%, with preservation of the testicular parenchyma and hormonal function, and avoidance of the delayed complications of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(90 citation statements)
references
References 9 publications
0
79
1
10
Order By: Relevance
“…Разрыв яичка определяется как разрыв белочной оболочки с выпячиванием семенных канальцев. Разрыв яичка обнаруживается приблизительно в 50% тупых травм мошонки [4]. Тупая травма мошонки может привести к вывиху яичка, разрыву яичка и/или подкожной гематоме мошонки.…”
Section: Discussionunclassified
“…Разрыв яичка определяется как разрыв белочной оболочки с выпячиванием семенных канальцев. Разрыв яичка обнаруживается приблизительно в 50% тупых травм мошонки [4]. Тупая травма мошонки может привести к вывиху яичка, разрыву яичка и/или подкожной гематоме мошонки.…”
Section: Discussionunclassified
“…Early surgical treatment of scrotal trauma is recommended by most authors. 4 Although, a thorough history and detailed clinical examination are essential for a precise diagnosis, ultrasonography with Doppler flow evaluation is the investigation of choice to detect scrotal abnormalities. 1 It is a non-invasive, simple and fast diagnostic tool with high accuracy in evaluating the integrity of scrotal contents, testicular integrity and blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In their series of 65 patients, Buckley and McAninch found a sensitivity of 100% and a specificity of 95% for ultrasonography in the diagnosis of testicular rupture. 4 Kim and colleagues demonstrated that loss of definition of the tunica albuginea is the only significant predictor for the diagnosis of testicular rupture in patients with blunt scrotal trauma. 5 There have only been 5 cases of testicular tumour rupture described in the literature in the last 60 years (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of nonperfusion related to extensive lacerocontusive injuries to the lower anterior mid-polar region at 35 00 (b) and minimal perfusion at 106 00 , which were not seen on the US study, and concomitant hematocele. Surgical treatment involves debridement and suturing of the tunica albuginea [1,3] and re-anastomosis of any microvessels that have been completely transected.…”
Section: Discussionmentioning
confidence: 99%